Community-Based Chinese Verbal Communication and Ethnic Malay in Jambi City - Yusnaini Yusnaini; Eraskaita Ginting (Jurnal Studi Sosial dan Politik, 2020)
This research departs from the curiosity of researchers related to the interaction process in intercultural communication, which is mostly influenced by differences in culture. Realizing excellent or effective communication with different cultural backgrounds, not as difficult as imagined and not as easy as many people think. When communicating and interacting in different cultures, many things must be considered and allow for misunderstandings. This study focused on verbal communication by using the theory of symbolic interaction to sharpen the analysis of verbal communication of ethnic Chinese and Malay ethnicity in controlling conflict in Jambi City. Data collection techniques included participant observer/observation, observation without participation, in-depth interviews, and documentation. The results of the study found a model of verbal communication that occurred between Chinese and Malay ethnic groups, namely the transactional model consisting of several components, namely language and how to speak. To realize effective communication, language, and ways of speaking have an essential role in capturing and conveying messages and symbols in verbal communication carried out.